APPLYING THE MURABAHA CONTRACT IN UZBEKISTAN FOR PURCHASING HOUSING: LEGAL AND FINANCIAL ASPECTS OF ISLAMIC MORTGAGE - A.A. Yo‘ldoshbekov (Scholar Express Journals, 2025)
This article examines the prospects of implementing Islamic mortgage instruments in Uzbekistan, with a particular focus on the Murabaha contract. Given the widespread public avoidance of interest-based financial products, the study highlights the legal, economic, and practical relevance of introducing a Sharia-compliant alternative to traditional mortgage financing. The Murabaha model is analyzed in detail, outlining its operational structure, key conditions under Islamic jurisprudence, and its application in various jurisdictions such as Bahrain, Malaysia, and Russia. The article also addresses legal challenges within Uzbekistan’s current banking regulations and offers recommendations for adapting the legal framework to accommodate Islamic finance. The study concludes that Murabaha-based Islamic mortgage financing has strong potential to contribute to financial inclusion and diversification in Uzbekistan, provided appropriate legislative measures are adopted.
Keywords: Islamic finance; Murabaha contract; Sharia-compliant mortgage